Spontaneous gait transition to high-speed galloping by reconciliation between body support and propulsion. (3rd August 2018) - Fukuhara, A.; Owaki, D.; Kano, T.; Kobayashi, R.; Ishiguro, A.
ABSTRACT: Quadrupeds change their gait patterns in response to locomotion speed to achieve low cost of transport over a wide range of speeds. Understanding the underlying control mechanism is essential to establish a design principle for legged robots that can adaptively generate energy-efficient locomotion patterns. Even decerebrate cats exhibit spontaneous gait transition, suggesting that adaptive gait patterns are generated via decentralized control systems, i.e. central pattern generators and reflexes. Several studies address this issue; however, the essential control mechanism that enables spontaneous transition from low- to high-speed gait is still poorly understood. To address this issue, this work reconsiders the interlimb coordination mechanism by focusing on two fundamental roles of limbs: body support and propulsion. To verify the proposed model, 2D simulations and 3D hardware experiments were conducted. The results indicate that the proposed model enables the robot to spontaneously exhibit gait transition to high-speed galloping and to achieve faster and more energy-efficient locomotion than a bounding gait in 3D hardware experiments. GRAPHICAL ABSTRACT: